Derivatives : - Whaley, Robert E. (Wiley, 2006)
Robert Whaley has more than twenty-five years of experience in the world of finance, and with this book he shares his hard-won knowledge in the field of derivatives with you. Divided into ten information-packed parts, Derivatives shows you how this financial tool can be used in practice to create risk management, valuation, and investment solutions that are appropriate for a variety of market situations.